A Retrospective Study on the Efficacy, Safety, and Effects on Systemic Inflammatory Markers of Combined Acupuncture Needle-Knife Therapy with Celecoxib Capsules for Discogenic Low Back Pain - Xu, Chaorong; Ren, Yanqing (Journal of Contemporary Medical Practice, 2025)
Purpose: To investigate the efficacy and safety of combined acupuncture and scalpel therapy with celecoxib capsules for discogenic low back pain, and to explore its effects on patients' neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and C-reactive protein (CRP). Method: A retrospective analysis was conducted on patients with discogenic low back pain treated with combined suture-needle knife therapy and celecoxib at our hospital. Paired-sample t-tests were used to compare changes in pain scores, lumbar function, and clinical symptom improvement before and after treatment. Concurrently, changes in peripheral blood inflammatory markers—neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and C-reactive protein (CRP)—were assessed pre- and post-intervention. Results: Of the 40 patients, 23 meeting the criteria were included in the analysis. Following two courses of acupuncture with thread implantation therapy, all patients demonstrated improvement in clinical symptoms, with significant reductions in pain NRS scores and OID indices compared to pre-treatment levels. One patient experienced needle syncope during treatment, which resolved after needle removal and rest; no other adverse events were observed. Following two treatment cycles, patients exhibited significantly reduced serum NLR and PLR levels, though CRP levels showed no marked decrease. Conclusion: The combination of acupuncture needle knife therapy with celecoxib proves safe and effective for treating discogenic low back pain, while also reducing changes in peripheral blood inflammatory markers. This suggests the treatment may exert its therapeutic effect on discogenic low back pain by modulating the inflammatory response.